Design explorations on the brake force distributions of a motorbike / M. Hisyam Basri ... [et al.] - Basri, M. Hisyam; Ismail, N.I.; Pahmi, Arif; Rabilah, R.; Sharudin, Hazim (Smart Manufacturing Research Institute (SMRI), 2025)
The braking system is crucial for motorbike safety, as effective braking ensures both deceleration and stability. This study investigates the influence of the deceleration rate and the combined biker and pillion load on the optimal distribution of the braking force of a motorbike. A full factorial experimental design was employed using Altair HyperStudy to evaluate the influence of key parameters on braking-force distribution. The study considered three design factors: deceleration (0.1 g, 0.55 g, and 1.0 g), biker mass (50 kg, 75 kg, and 100 kg), and pillion mass (0 kg, 50 kg, and 100 kg). Results indicated a significant positive linear relationship between these parameters and brake forces, with deceleration as the most influential factor. An increase in deceleration resulted in a substantial rise in front brake force, up to 1753.22 N, while biker and pillion masses increased front brake force by 241.22 N and 350.69 N, respectively. Interaction effects revealed that the deceleration, in combination with the pillion load, produced a front brake force of 2226.64 N at 1g deceleration, while biker interaction resulted in 2091.47 N. For rear brake force, deceleration and pillion interaction yielded 64.28 N, highlighting its sensitivity to pillion at higher decelerations. Analysis of Variance (ANOVA) confirmed the statistical significance of all parameters, emphasizing deceleration as critical. Optimal brake force distribution relies on deceleration, necessitating balanced braking to enhance efficiency and safety, achievable through synchronized braking mechanisms like the Concurrent Brake Actuator (CBA).